Սիրաքի գրքի հայերեն թարգմանությունը - Խմբ.՝ Առաքել Առաքելյան (1944-1948); Լևոն Կիսիբեկյան (1948-1950); Աշոտ Աբրահամյան (1950-1955); Առաքել Առաքելյան (1955-1956); Արթուն Հատիտյան (1956-1982); Պարգեւ Շահբազյան (1983-1984); Երվանդ Մելքոնյան (1985-1993); Տ. Ասողիկ եպս. Արիստակեսյան (1994-1996); Տ. Բագրատ աբղ. Գալստյան (1996-1998); Մարիամ Վարդանյան (պաշտոնակատար) (1998-1999); Տ. Արշակ աբղ. Խաչատրյան (պաշտոնակատար) (1999); Անդրանիկ Զեյթունյան (2000-2001); et al. (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В статье предусматривается устойчивый богословский анализ армянской версии перевода книги Сираха. Роль и место этой книги в каноне армянского перевода Библии на протяжении многих веков была спорной. Автор уделяет большое внимание текстовой оценке книги Сираха на армянском языке. This article provides a sustained theological analysis of the Armenian version of the Book of Sirach. The role and place of the latter in the canon of the Armenian translation of the Bible has for centuries been disputed. The author places a great emphasis on the textual evaluation of Sirach in Armenian.
Keywords: Language and Literature; Translation and interpretation